An experimental evaluation between pure and diluted MQL versus flood lubri-cooling focused on cost and environmental impact - Lopes, José Claudio [UNESP]; Talon, Anthony Gaspar [UNESP]; Rodrigues, Matheus de Souza [UNESP]; Moretti, Guilherme Bressan [UNESP]; Machado, Felipe de Carvalho [UNESP]; Souza, Guilherme Guerra de [UNESP]; Ribeiro, Fernando Sabino Fonteque [UNESP]; Sanchez, Luiz Eduardo de Angelo [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2023)
In machining processes, cutting fluid presents itself as a fundamental component, as they are responsible for the refrigeration and lubrication of the cutting interface. This is especially true for grinding processes, as the heat generated is so intense that it can cause thermal damage to the workpiece, changing its microstructure and mechanical properties. The application of the fluid in the process also helps with a better surface finishing and integrity of the workpiece with little geometric inaccuracies. However, its usage may cause damage to the health of the operators and the environment, as there is presence of toxic additives to improve the cutting fluid’s efficacy. While the most common method used with cutting fluid is the flood method, which consists in applying large quantities of pure oil or oil emulsified in water, one of the more eco-friendly alternatives is the minimum quantity lubrification (MQL) that uses a small amount of oil pulverized in the cutting surface with the usage of a jet of compressed air, achieving, in many cases, results similar to the flood method due to the technique’s excellent lubricating capability. On the other hand, this method presents some challenges to overcome, such as the lower cooling capacity and wheel clogging due to hot chips. To circumvent such obstacles, two techniques were found: adding water to the cutting fluid and a wheel cleaning system (jet of compressed air aimed at the surface of the grinding wheel to remove the chips clogged in the wheel pores). This paper analyzes the use of water paired with the MQL method in the external cylindrical plunge grinding of alumina (Al2O3) to minimize the flaws of the technique. The parameters evaluated include surface roughness (Ra), roundness error, diametrical wheel wear, grinding power, pollution analysis, and cost analysis for flood method, MQL with pure oil (1:0), and MQL with water in 1:1, 1:3, and 1:5 oil–water proportions, with and without wheel cleaning jet. MQL with pure oil generated the worst results, while diluted MQL presented better results. The use of diluted MQL 1:5 with wheel cleaning jet (WCJ) brought results that approximated most of the conventional method, with a fraction of the pollution and cost, showing the potential for using MQL with WCJ as an alternative to the flood method in the industry. However, high cutting temperatures and wheel clogging in MQL still pose obstacles, requiring more research in this method to improve it even further its efficiency.
Keywords: Ceramic; Cutting fluid; Environment; Greenhouse; Grinding; MQL